Pneumatic conveying design guide - Mills, David (Elsevier/Butterworth-Heinemann, 2004)
The Pneumatic Conveying Design Guide will be of use to both designers and users of pneumatic conveying systems. Each aspect of the subject is discussed from basic principles to support those new to, or learning about, this versatile technique. The Guide includes detailed data and information on the conveying characteristics of a number of materials embracing a wide range of properties. The data can be used to design pneumatic conveying systems for the particular materials, using logic diagrams for design procedures, and scaling parameters for the conveying line configuration. Where pneumatic conveyors already exist, the improvement of their performance is considered, based on strategies for optimizing and up-rating, and the extending of systems or adapting them for a change of material is also considered. All aspects of the pneumatic conveying system are considered, such as the type of material used, conveying distance, system constraints including feeding and discharging, health and safety requirements, and the need for continuous or batch conveying. * Highly practical, enabling suppliers and users to choose, design, and build suitable systems with a high degree of confidence * Health and safety requirements taken into consideration in the safe conveying methods described in this book * Practical application combined with background theory makes this an excellent resource for those learning about the topic.